In Vitro And Ex Vitro Propagation Of A Wild-Extinct Fern Lygodium Circinnatum (Burn.F) Sw. Grown In Bali - Rindang Dwiyani (Bumi Lestari Journal of Environment, 2016)
Research concerning of propagation of a wild-extinct fern Lygodium circinnatum had been done at Faculty of Agriculture, Udayana University, Denpasar Bali Indonesia. At some places in Indonesia, as well as Bali, this species is used as materials for making handicraft. In Bali, the species grows wildly in the forest and it is almost extinct due to over gathering. This study aimed to find out method for domestication of L. circinnatum, therefore this wild species can be cultivated, provided materials for making handicraft and might solve the problem of extinction. Various media for growing spores of L. circinnatum in vitro and ex vitro were trialed. In conclusion, full strength of MS media without sugar was the most appropriate media for growth and development of spores of L. circinnatum in vitro. While for ex vitro, the appropriate media were paddy silt-soil and decomposed leaf either with or without addition of foliar fertilizer. However, we suggested ex-vitro cultivation was more appropriate, the technique was much easier and the spores grew faster compared to those of in-vitro.